2019
DOI: 10.1007/s13213-019-01504-4
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus halotolerans strain LYSX1-induced systemic resistance against the root-knot nematode Meloidogyne javanica in tomato

Abstract: Purpose Determination of the nematicidal potential and mode of action of bacteria isolated from tobacco rhizosphere soil against the root-knot nematode Meloidogyne javanica in tomato plants. Methods Antagonistic bacteria were isolated from rhizosphere soil of tobacco infested with root-knot nematodes. Culture filtrate was used to examine nematicidal activity and ovicidal action of bacterial strains. Biocontrol of M. javanica and growth of treated tomato plants were assessed in pot experiments. To clarify wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…Moreover, culture filtrates of bacterial strain QTH8 demonstrated antagonistic potential against Heterodera glycines , Meloidogyne javanica , and M. incognita (data not shown). Similar findings have been documented by Xia et al (2019), who found broad-spectrum activity of B. halotolerans LYSX1 against diverse plant pathogens [ 31 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, culture filtrates of bacterial strain QTH8 demonstrated antagonistic potential against Heterodera glycines , Meloidogyne javanica , and M. incognita (data not shown). Similar findings have been documented by Xia et al (2019), who found broad-spectrum activity of B. halotolerans LYSX1 against diverse plant pathogens [ 31 ].…”
Section: Discussionsupporting
confidence: 89%
“…The outcomes from the glasshouse environment indicated that the application of QTH8 improved the growth parameters of wheat seedlings (root length, plant height, and fresh plant weight) and reduced the severity of the disease caused by F. pseudograminearum . Several research groups have reported similar findings [ 17 , 18 , 19 , 31 ]. However, it is essential to verify the potential of QTH8 against F. pseudograminearum under field tests in future research.…”
Section: Discussionsupporting
confidence: 62%
“…Many studies have reported that plant-parasitic nematodes can be controlled through active substances generated by bacteria during the fermenting process [ 7 , 11 , 13 , 17 , 27 , 28 , 29 , 30 ]. Specifically, several pathogenic E. coli isolates have been assessed for their ability to kill the free-living nematode C. elegans [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, B. thuringiensis (Bt) produces the well-known Cry protein, which displays specific toxic activity against nematodes and insects [ 15 ]. In addition, induced systemic resistance (ISR) is triggered by plant growth-promoting rhizobacteria (PGPR) [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…in the world. The nematode causes gall at the root systems and impairs the absorption of water and minerals, which results in wilting, growth suppression, reduction in yield, and eventually death (Xia et al 2019). The application of non-host plants, rotation, resistant plants, flooding, and nematicides is methods for the management of plant-parasitic nematodes.…”
Section: Introductionmentioning
confidence: 99%